Dutch Disease and Spending Strategies in a Resource-Rich Low-Income Country The Case of Niger - Go, Delfin S. (The World Bank, 2013)
This paper examines spending plans suggested by the recent literature regarding Dutch disease and examines their implications to Niger relative to its expanding mineral sector. The key to the benefits of significant mineral revenue lies with the productivity and supply responses of spending. If significant output gain is ensured, then there is little difference across the spending plans in their effects on real consumption. The overshooting of relative prices of the non-tradable sector or the shrinking share of traded sectors in gross domestic product is also ameliorated with greater supply flexibility. Growth paths of alternative spending strategies differ markedly in timing and pattern when spending does not raise productivity. As a caution against expectations that exaggerate the benefits of mineral revenue under all circumstances, the more aggressive spending plan may result in a boom-bust cycle if fiscal adjustments and debt repayments are necessary for any significant borrowing against future revenue and productivity gains are not realized. Using extractive industries revenue for transfers to households would have a greater effect on poverty reduction in the short and medium term but the long-run gains from investment in human and physical capital are likely to offset the initial lack of pro-poor bias. Different strategies differ significantly with regard to risks and required technical implementation capacity and political capacity to sustain a chosen course of action